PENGARUH KEPEMIMPINAN DAN REWARD TERHADAP KINERJA KARYAWAN PADA PT. SUMBAHAN WIRAKARTIKA KRAMATWATU - Tabroni Tabroni; Mamay Komarudin (Gapenas Publisher, 2021)
Companies that want to develop and adapt to the conditions of the times must improve the quality of human resources within the company. With the increase in the quality of human resources in the company, it will automatically make employees carry out their work professionally, responsibly, and have a good attitude to help companies meet the needs of an increasingly complex society in this era of globalization.This study aims to determine whether there is an influence of leadership on employee performance at PT. Sumbahan Wirakartika Kramatwatu and to find out whether there is an effect of reward on employee performance at PT. Wirakartika Kramatwatu's contribution and to find out whether there is a simultaneous influence of leadership and reward on employee performance at PT. Sumbahan Wirakartika Kramatwatu. The research method used is quantitative - descriptive which discusses three variables, namely leadership and reward as independent variables and employee performance as the dependent variable. With a population of 88 employees and using a saturated sample so that the number of samples is 88 employees. Based on the calculation results, it was obtained that the partial t-test of leadership on performance obtained the results of t-count greater than t-table (10.278>1.988) and partial t-test of reward on performance obtained by t-test greater than t-table (4,672 > 1,988), as well as test- F leadership and performance rewards are obtained F count results are greater than F table (106.227>3.10). Referring to the test results, it can be concluded that leadership partially affects performance and rewards partially affect performance, and leadership and rewards simultaneously affect performance. In addition, it is also known based on the above test that simultaneously leadership and rewards affect performance by 72.4%,